2007
DOI: 10.30638/eemj.2007.012
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Alcian Blue 8 Gx by Heterogeneous and Homogeneous Photocatalytic Processes

Abstract: The photocatalytic degradation of Alcian Blue 8 GX, a copper phthalocyanine cationic dye, has been investigated in aqueous solutions both in heterogeneous and homogeneous systems. Initial colour removal rates in different conditions were calculated in both cases. Influence of amounts of H 2 O 2 and FeCl 3 was studied and compared for the two photocatalytic systems. Finally, some conclusions regarding the efficiency of the two photocatalytic processes were established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Indigo Carmine is also used as dye in food and cosmetics industry. Several processes have been suggested for removal of Indigo Carmine and other dyes from wastewater including adsorption (Kyzas et al, 2012), photochemical (Caliman et al, 2007) and electrochemical methods Flox et al, 2006;Secula et al, 2011;Dogan & Turkdemir, 2012;Hammami et al, 2012). Dogan & Türkdemir, 2005, reported an almost 100% removal of color and 60% of COD from an 0.1 w/v aqueous indigo carmine solution in 90 min.…”
Section: Introductionmentioning
confidence: 99%
“…Indigo Carmine is also used as dye in food and cosmetics industry. Several processes have been suggested for removal of Indigo Carmine and other dyes from wastewater including adsorption (Kyzas et al, 2012), photochemical (Caliman et al, 2007) and electrochemical methods Flox et al, 2006;Secula et al, 2011;Dogan & Turkdemir, 2012;Hammami et al, 2012). Dogan & Türkdemir, 2005, reported an almost 100% removal of color and 60% of COD from an 0.1 w/v aqueous indigo carmine solution in 90 min.…”
Section: Introductionmentioning
confidence: 99%
“…What is reported refers to electrocoagulation of the non sulfonated parent copper phthalocyanine [21], photo-degradation of di-or tetrasulfonated phthalocyanine [8,9,13] and ultrasound degradation of parent phthalocyanine [11].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional biological and oxidation treatment processes are often less successful because these dyes are barely or non biodegradable [9,12]. Degradation of copper phthalocyanines by heterogenous or homogenous photocatalytic processes [13] and UV irradiation in the presence of H 2 O 2 [8,9] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The discharge of dye waste and effluent containing parent remains a problem. Degradation of copper phthalocyanines by heterogenous or homogenous photocatalytic processes [136] and UV irradiation in the presence of H 2 O 2 have been reported [143,153]. Electrochemical processes for pollution abatement have been proven viable alternatives or complementary to biological treatment in some instances, especially when pollutants are recalcitrant to biological processing.…”
Section: Chapter 1 11 State Of the Artmentioning
confidence: 99%
“…Conventional biological treatment processes are often less successful because these dyes are barely or non biodegradable (Beydill et al, 2001;Cailean et al, 2009a;2009b;Lei et al, 1997;Savin and Butnaru, 2009;. Degradation of copper phthalocyanines by heterogenous or homogenous photocatalytic processes (Caliman et al, 2007) and UV irradiation in the presence of H 2 O 2 have been reported (Dos Santos and Masini, 2009;Shu and Chang, 2005). Electrochemical processes for pollution abatement have been proven viable alternatives or complementary to biological treatment in some instances, especially when pollutants are recalcitrant to biological processing.…”
Section: Introductionmentioning
confidence: 99%